Understanding Bitcoin : Cryptography, Engineering and Economics - Franco, Pedro (Chichester, West Sussex : Wiley, 2015)
Discover Bitcoin, the cryptocurrency that has the finance world buzzing Bitcoin is arguably one of the biggest developments in finance since the advent of fiat currency. With Understanding Bitcoin, expert author Pedro Franco provides finance professionals with a complete technical guide and resource to the cryptography, engineering and economic development of Bitcoin and other cryptocurrencies. This comprehensive, yet accessible work fully explores the supporting economic realities and technological advances of Bitcoin, and presents positive and negative arguments from various economic schools.
CHAPTER 10 The Origins of Bitcoin10.1 David Chaum's Ecash; 10.2 Adam Back's Hashcash; 10.3 Nick Szabo's bit gold and Wei Dai's b-money; 10.4 Sander and Ta-Shma's Auditable, Anonymous Electronic Cash; 10.5 Hal Finney's RPOW; 10.6 Satoshi Nakamoto; CHAPTER 11 Alt(ernative) Coins; 11.1 Litecoin; 11.2 Peercoin; 11.3 Namecoin; 11.4 Auroracoin; 11.5 Primecoin; 11.6 Dogecoin; 11.7 Freicoin; 11.8 Other Alt-coins; 11.9 The Case For/Against Alt-coins; CHAPTER 12 Contracts (the Internet of Money or Cryptocurrencies 2.0); 12.1 Digital Assets; 12.2 Smart Property; 12.3 Micropayments.
Includes bibliographical references and index.
Keywords: Money; Electronic funds transfers; Electronic commerce; Data encryption (Computer science); Computer networks -- Security measures; Computer security; Data encryption (Computer science); Engineering; COMPUTERS -- Internet -- Security; COMPUTERS -- Networking -- Security; COMPUTERS -- Security -- General; Data encryption (Computer science); Electronic commerce; Electronic funds transfers; Money; Electronic books